Keris Batik Industry Development Strategy to Support Local Economic Growth - Purnamasari, Putri; Nirwana, Dwi; Selvianti, Nadia; Saputra, Bima; Susanti, Marlina; Yolandari, Poppy Intan; Siswantoro, Ariel (Central Community Development Journal, 2023)
The Keris batik industry is a company engaged in the production and sale of batik fabric. The Keris batik industry produces batik fabrics with both traditional and modern motifs. They are known for their distinctive batik designs and high quality. Keris batik is also renowned for combining Indonesian batik traditions with a modern touch, resulting in products that are in demand both domestically and internationally. This company is also involved in the promotion and preservation of Indonesian batik culture. Keris Batik collaborates with various countries, especially those interested in promoting culture and handicrafts. Countries that frequently collaborate with Indonesian batik producers include Malaysia, Japan, the Netherlands, and several countries in the Middle East and Europe, which are attracted to the beauty and cultural value of Indonesian batik. The Keris batik industry plays a crucial role in developing Indonesia's cultural heritage by contributing to the development of culture where the industry can develop products inspired by Indonesia's cultural heritage such as handicrafts, traditional textiles, and performing arts. This way, the industry not only maintains cultural values but also creates new job opportunities, training, and education. The industry can also integrate modern technology into the production and promotion of cultural products. Moreover, partnerships with local communities ensure that cultural product development is conducted with respect and preservation of traditional values. Such collaborations create a balance between innovation and cultural preservation. Keris Batik adheres to high-quality standards, from the selection of high-quality raw materials, craftsmen’s skills, motif and design selection, safe color choices, quality control, to innovation and development. All these factors combined give Keris batik a unique appeal and value that is not only commercial but also holds deep cultural and social significance for both the Indonesian community and the world. The research findings indicate that a growth strategy is necessary to develop the batik industry. The expected development strategy aims to enhance competitiveness in production related to local economic growth by leveraging creativity and modern technology, which play an essential role in the development of the Keris batik industry.